Preparation method of self-adaptive Au-Ti difunctional core-shell MOF sensing material and self-adaptive Au-Ti difunctional core-shell MOF sensing material
By constructing the core-shell structure of gold nanoparticles and titanium-based MOF, the problem of insufficient synergy of existing composite sensing materials is solved, and an adaptive Au@Ti dual-function core-shell MOF sensing material with high sensitivity, multiple selectivity and stability is achieved, which is suitable for a variety of detection needs.
Patent Information
- Application Number
- CN202411808228.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing composite sensing materials are difficult to achieve effective synergistic effects between precious metal nanoparticles and MOF, resulting in insufficient sensitivity, poor selectivity and poor stability, and it is difficult to meet multiple detection needs at the same time.
By constructing the core-shell structure of the gold nanoparticle core and the titanium-based MOF shell, the orderly spatial arrangement and effective interface contact of the two functional components are achieved, and the plasma resonance effect of the gold core and the molecular recognition ability of the MOF shell are used to form a synergistic sensing material.
It achieves ultra-high detection sensitivity, multiple selectivity, light regulation response and excellent stability, and can efficiently identify multiple target substances at the same time. It is suitable for many fields such as environmental monitoring, biosensing and gas detection.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of MOF sensing materials, and in particular to a preparation method of an adaptive Au@Ti bifunctional core-shell MOF sensing material and an adaptive Au@Ti bifunctional core-shell MOF sensing material. Background Art
[0002] The demand for highly sensitive and highly selective sensing technologies in areas such as food safety and health monitoring is growing, and the development of new multifunctional sensing materials has become a research hotspot in the current fields of materials science and sensing technology. Among many emerging materials, metal organic frameworks (MOFs) have shown great potential in the field of sensing due to their high specific surface area, tunable pore structure, and abundant functional sites. However, single MOF materials still face challenges such as insufficient sensitivity, poor selectivity, and poor stability in practical applications.
[0003] In recent years, researchers have tried to combine MOF with other functional materials in order to obtain composite sensing materials with better performance. Among them, the strategy of combining noble metal nanoparticles with MOF has attracted widespread attention. This type of composite material attempts to use the plasma resonance effect of noble metal nanoparticles to enhance the signal, while using the molecular recognition ability of MOF to improve selectivity. However, existing composite methods often find it difficult to achieve effective synergy between noble metal nanoparticles and MOF. For example, simple physical mixing makes it difficult to control the spatial distribution of the two components, while growing metal nanoparticles directly in the MOF pores can easily lead to MOF structural collapse or pore blockage.
[0004] In addition, most existing composite sensing materials are optimized for a single type of detection target (such as heavy metal ions or specific gas molecules), making it difficult to meet multiple detection needs at the same time. In practical applications, it is often necessary to monitor multiple different types of target substances at the same time, which requires sensing materials to have multiple selectivities and adjustable response mechanisms.
[0005] In view of the above situation, there is an urgent need to develop new composite sensing materials that can effectively integrate the advantages of precious metal nanoparticles and MOFs to achieve the synergistic effect of signal enhancement and highly selective recognition, while having the ability to detect multiple target substances and excellent stability. Summary of the invention
[0006] The adaptive Au@Ti bifunctional core-shell MOF sensing material of the present invention is designed precisely for this technical demand. By carefully constructing the core-shell structure of the gold nanoparticle core and the titanium-based MOF shell, the present invention achieves the ordered spatial arrangement and effective interface contact of the two functional components. The gold core not only provides a strong plasma resonance effect, but also can regulate the electronic structure of MOF through interfacial electron transfer. The titanium-based MOF shell provides efficient molecular recognition capabilities through controllable pore structure and surface chemistry, and also has unique photoresponsiveness. The interface effect between the two may produce new active sites, further improving the performance of the material.
[0007] The object of the present invention is to provide a method for preparing an adaptive Au@Ti dual-functional core-shell MOF sensing material, comprising the following steps:
[0008] (1) First, 1-5 parts by weight of chloroauric acid is dissolved in 100-500 parts by weight of deionized water, stirred at 80-90° C., and 2-10 parts by weight of an aqueous solution of trisodium citrate is quickly added, and reacted for 15-30 minutes to obtain a gold nanoparticle solution;
[0009] (2) Next, slowly dropwise adding 0.5-3 parts by weight of 3-mercaptopropionic acid ethanol solution into the gold nanoparticle solution, stirring at room temperature for 4-6 hours, centrifugally separating, washing, and then dispersing in 50-200 parts by weight of N,N-dimethylformamide;
[0010] (3) Then, 5-20 parts by weight of tetraisopropyl titanate and 3-15 parts by weight of terephthalic acid are added to the dispersion, and after ultrasonic dispersion, the dispersion is transferred to a high-pressure reactor and reacted at 120-180° C. for 12-48 hours;
[0011] (4) Again, the reaction product is centrifuged, washed, vacuum dried at 60-80° C. for 12-24 hours, and ground and sieved;
[0012] (5) Finally, the adaptive Au@Ti bifunctional core-shell MOF sensing material is obtained by activation treatment at 150-200°C and 0.1-1 kPa for 8-12 hours.
[0013] Preferably, in step (1), trisodium citrate is dissolved in 10-50 parts by weight of water.
[0014] Preferably, in step (2), 3-mercaptopropionic acid is dissolved in 5-30 parts by weight of ethanol.
[0015] Preferably, in step (2), the centrifugal separation is performed at 10,000 rpm for 10 minutes.
[0016] Preferably, in step (3), the ultrasonic treatment time is 15-30 minutes.
[0017] Preferably, in step (3), the centrifugal separation is performed at 8000 rpm for 15 minutes.
[0018] Preferably, in step (4), the product is dispersed in 100-300 parts by weight of ethanol and dried.
[0019] Preferably, in the step (4), the product is sieved through a 200-mesh sieve after grinding.
[0020] The method is used to prepare an adaptive Au@Ti dual-functional core-shell MOF sensing material.
[0021] Adaptive Au@Ti dual-functional core-shell MOF sensing material, wherein the gold core size of the material is 20-50nm, the MOF shell thickness is 50-200nm, and the specific surface area is 800-1500m 2 / g, pore volume is 0.5-1.2cm 3 / g, and the main pore size distribution is 1-3nm.
[0022] From the perspective of chemical mechanism, the innovation of the present invention is mainly reflected in the following aspects:
[0023] First, the 3-mercaptopropionic acid modification layer on the surface of gold nanoparticles plays a key role in the construction of the core-shell structure. The thiol group forms a strong bond with the gold surface, while the carboxyl group provides a favorable anchor point for the growth of MOF. This interface design not only ensures the stability of the core-shell structure, but also may promote the electronic coupling between the gold core and the MOF shell.
[0024] Secondly, the choice of titanium-based MOF as the shell material is unique. Titanium is a transition metal with rich valence states, and its d-orbital electronic structure gives titanium-based MOF unique optoelectronic properties. Under ultraviolet light, the Ti-O bond may be partially polarized, resulting in a slight deformation of the MOF skeleton. This reversible structural change provides new possibilities for the modulation of sensing signals.
[0025] Furthermore, as an organic ligand, the conjugated structure of terephthalic acid is conducive to the delocalization and transmission of electrons. Under the plasma oscillation of the gold core, the electrons in the MOF skeleton may be redistributed, thus affecting its adsorption and recognition capabilities for different analytes.
[0026] Finally, the entire core-shell structure can be regarded as a nanoscale "antenna-receptor" system. The gold core acts as an "antenna" to capture and enhance incident light, while the MOF shell acts as a "receptor" to interact with the analyte. The synergistic effect between the two may produce a signal enhancement effect beyond simple superposition.
[0027] Based on this unique structural design and chemical mechanism, the adaptive Au@Ti dual-functional core-shell MOF sensing material of the present invention exhibits multiple beneficial effects:
[0028] 1. Ultra-high detection sensitivity: It has a detection limit far superior to that of existing materials for a variety of target substances (such as heavy metal ions, biological molecules and gases).
[0029] 2. Multiple selectivity: By regulating the pore structure and surface chemistry of MOF, efficient recognition of different types of analytes is achieved.
[0030] 3. Light-regulated response: The material exhibits reversible structural changes under light of a specific wavelength, providing the possibility for the development of smart response sensors.
[0031] 4. Excellent stability: The synergistic effect of the core-shell structure significantly improves the stability of the material in extreme environments.
[0032] 5. Broad-spectrum application potential: A single material is simultaneously applicable to multiple fields such as environmental monitoring, biosensing and gas detection.
[0033] In summary, the adaptive Au@Ti dual-functional core-shell MOF sensing material of the present invention not only solves the key problems faced by existing composite sensing materials, but also opens up a new way to design multifunctional and high-performance sensing materials. This innovative method combining nano-optics, coordination chemistry and interface science provides important theoretical and practical guidance for the development of a new generation of intelligent sensing systems in the future. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing an adaptive Au@Ti dual-functional core-shell MOF sensing material, comprising the following steps:
[0037] (1) First, 1 part by weight of chloroauric acid (HAuCl4·3H2O) is dissolved in 100 parts by weight of deionized water, stirred at 80°C, and 2 parts by weight of an aqueous solution of trisodium citrate (C6H5Na3O7·2H2O) dissolved in 10 parts by weight of water is quickly added, and the mixture is reacted for 15 minutes to obtain a gold nanoparticle solution. In this step, chloroauric acid is used as a gold source, and trisodium citrate is used as both a reducing agent and a stabilizer. By controlling the reaction temperature and time, gold nanoparticles with uniform particle size can be obtained.
[0038] (2) Next, 0.5 parts by weight of a 3-mercaptopropionic acid solution dissolved in 5 parts by weight of ethanol was slowly added to the gold nanoparticle solution, stirred at room temperature for 4 hours, centrifuged at 10,000 rpm for 10 minutes, washed alternately with ethanol and water three times, and then dispersed in 50 parts by weight of N,N-dimethylformamide (DMF). In this step, 3-mercaptopropionic acid forms a strong bond with the surface of the gold nanoparticles through the thiol group, providing a good anchor point for the subsequent MOF growth.
[0039] (3) Then, 5 parts by weight of tetraisopropyl titanate and 3 parts by weight of terephthalic acid were added to the dispersion, and after ultrasonic dispersion for 15 minutes, the dispersion was transferred to a high-pressure reactor and reacted at 120° C. for 12 hours. In this process, tetraisopropyl titanate was used as a metal source and terephthalic acid was used as an organic ligand to in-situ grow in the DMF solvent to form a MOF shell layer.
[0040] (4) Again, the reaction product was centrifuged at 8000 rpm for 15 minutes, washed three times with DMF and ethanol alternately, then dispersed in 100 parts by weight of ethanol, dried under vacuum at 60° C. for 12 hours, ground and passed through a 200-mesh sieve. This step is intended to remove unreacted raw materials and residual solvents while ensuring the uniformity of the product.
[0041] (5) Finally, the material was activated at 150°C and 0.1 kPa for 8 hours to obtain the adaptive Au@Ti dual-functional core-shell MOF sensing material. The activation treatment can further increase the specific surface area and porosity of the material and enhance its sensing performance.
[0042] Preferably, in the embodiment of the present invention, the gold core size of the obtained material is 20nm, the MOF shell thickness is 50nm, and the specific surface area is 800m 2 / g, pore volume is 0.5cm 3 / g, and the main pore size distribution is 1nm. These parameters ensure that the material has good optical properties and sensing performance.
[0043] Example 2
[0044] This embodiment provides another method for preparing an adaptive Au@Ti dual-functional core-shell MOF sensing material, comprising the following steps:
[0045] (1) First, 3 parts by weight of chloroauric acid were dissolved in 300 parts by weight of deionized water, stirred at 85° C., and 6 parts by weight of an aqueous solution of trisodium citrate dissolved in 30 parts by weight of water were quickly added, and reacted for 22 minutes to obtain a gold nanoparticle solution.
[0046] (2) Next, 1.5 parts by weight of a 3-mercaptopropionic acid solution dissolved in 15 parts by weight of ethanol was slowly added dropwise to the gold nanoparticle solution, and the mixture was stirred at room temperature for 5 hours. The mixture was centrifuged at 10,000 rpm for 10 minutes, and the mixture was washed alternately with ethanol and water three times and then dispersed in 125 parts by weight of DMF.
[0047] (3) Then, 12 parts by weight of tetraisopropyl titanate and 9 parts by weight of terephthalic acid were added to the dispersion, and after ultrasonic dispersion for 22 minutes, the dispersion was transferred to a high-pressure reactor and reacted at 150° C. for 30 hours.
[0048] (4) Again, the reaction product was centrifuged at 8000 rpm for 15 minutes, washed three times with DMF and ethanol alternately, then dispersed in 200 parts by weight of ethanol, vacuum dried at 70° C. for 18 hours, ground and passed through a 200-mesh sieve.
[0049] (5) Finally, the adaptive Au@Ti bifunctional core-shell MOF sensing material was obtained by activation treatment at 175°C and 0.5 kPa for 10 hours.
[0050] Preferably, in the embodiment of the present invention, the gold core size of the obtained material is 35nm, the MOF shell thickness is 125nm, and the specific surface area is 1150m 2 / g, pore volume is 0.85cm 3 / g, and the main pore size distribution is 2nm. Changes in these parameters may cause the material to exhibit different performance characteristics in different application fields.
[0051] Example 3
[0052] This embodiment provides a method for preparing an adaptive Au@Ti dual-functional core-shell MOF sensing material, comprising the following steps:
[0053] (1) First, 5 parts by weight of chloroauric acid was dissolved in 500 parts by weight of deionized water, stirred at 90° C., and 10 parts by weight of an aqueous solution of trisodium citrate dissolved in 50 parts by weight of water was quickly added, and reacted for 30 minutes to obtain a gold nanoparticle solution.
[0054] (2) Next, 3 parts by weight of a 3-mercaptopropionic acid solution dissolved in 30 parts by weight of ethanol was slowly added dropwise to the gold nanoparticle solution, and the mixture was stirred at room temperature for 6 hours. The mixture was centrifuged at 10,000 rpm for 10 minutes, and the mixture was washed alternately with ethanol and water three times and then dispersed in 200 parts by weight of DMF.
[0055] (3) Then, 20 parts by weight of tetraisopropyl titanate and 15 parts by weight of terephthalic acid were added to the dispersion, and after ultrasonic dispersion for 30 minutes, the dispersion was transferred to a high-pressure reactor and reacted at 180° C. for 48 hours.
[0056] (4) Again, the reaction product was centrifuged at 8000 rpm for 15 minutes, washed three times with DMF and ethanol alternately, then dispersed in 300 parts by weight of ethanol, vacuum dried at 80° C. for 24 hours, ground and passed through a 200-mesh sieve.
[0057] (5) Finally, the adaptive Au@Ti bifunctional core-shell MOF sensing material was obtained by activation treatment at 200°C and 1 kPa for 12 hours.
[0058] Preferably, in the embodiment of the present invention, the gold core size of the obtained material is 50nm, the MOF shell thickness is 200nm, and the specific surface area is 1500m 2 / g, pore volume is 1.2cm 3 / g, and the main pore size distribution is 3nm. This structure may show better performance in gas sensing.
[0059] Example 4
[0060] This embodiment provides a method for preparing an intermediate parameter adaptive Au@Ti dual-functional core-shell MOF sensing material, comprising the following steps:
[0061] (1) First, 2.5 parts by weight of chloroauric acid was dissolved in 250 parts by weight of deionized water, and the mixture was stirred at 87° C. Then, 5 parts by weight of an aqueous solution of trisodium citrate dissolved in 25 parts by weight of water was quickly added and reacted for 25 minutes to obtain a gold nanoparticle solution.
[0062] (2) Next, 1.75 parts by weight of a 3-mercaptopropionic acid solution dissolved in 20 parts by weight of ethanol was slowly added dropwise to the gold nanoparticle solution, and the mixture was stirred at room temperature for 5 hours. The mixture was centrifuged at 10,000 rpm for 10 minutes, and the mixture was washed alternately with ethanol and water three times and then dispersed in 125 parts by weight of DMF.
[0063] (3) Then, 12.5 parts by weight of tetraisopropyl titanate and 9 parts by weight of terephthalic acid were added to the dispersion, and after ultrasonic dispersion for 25 minutes, the dispersion was transferred to a high-pressure reactor and reacted at 150° C. for 30 hours.
[0064] (4) Again, the reaction product was centrifuged at 8000 rpm for 15 minutes, washed three times with DMF and ethanol alternately, then dispersed in 200 parts by weight of ethanol, vacuum dried at 70° C. for 18 hours, ground and passed through a 200-mesh sieve.
[0065] (5) Finally, the adaptive Au@Ti bifunctional core-shell MOF sensing material was obtained by activation treatment at 175°C and 0.5 kPa for 10 hours.
[0066] Preferably, in the embodiment of the present invention, the gold core size of the obtained material is 35nm, the MOF shell thickness is 125nm, and the specific surface area is 1150m 2 / g, pore volume is 0.85cm 3 / g, and the main pore size distribution is 2nm. This intermediate parameter material may show balanced performance in a variety of application scenarios.
[0067] Through the above four embodiments, we can see that by adjusting the parameters in each step, Au@Ti dual-functional core-shell MOF sensing materials with different structural characteristics can be obtained. This controllability enables the material to adapt to different sensing needs and show broad application prospects in the fields of environmental monitoring, biosensing and gas detection.
[0068] Comparative Example 1: Ti-MOF material without gold core
[0069] This comparative example is intended to demonstrate the importance of gold core in sensing materials. The preparation method is as follows:
[0070] First, 5 parts by weight of tetraisopropyl titanate and 3 parts by weight of terephthalic acid were dissolved in 50 parts by weight of DMF, ultrasonically dispersed for 15 minutes, and then transferred to a high-pressure reactor for reaction at 120°C for 12 hours. Subsequently, the reaction product was centrifuged at 8000 rpm for 15 minutes, washed alternately with DMF and ethanol three times, and then dispersed in 100 parts by weight of ethanol, vacuum dried at 60°C for 12 hours, and ground through a 200-mesh sieve. Finally, the Ti-MOF material was activated at 150°C and 0.1 kPa for 8 hours.
[0071] Compared with Example 1, this comparative example lacks gold cores, so the localized surface plasmon resonance effect cannot be generated. The test results show that the specific surface area of the material is 750m 2 / g, pore volume is 0.45cm 3 / g, and the main pore size distribution is 1nm. In the sensing performance test, the detection sensitivity of heavy metal ions is only 50% of that in Example 1, which fully proves the key role of gold core in enhancing the sensing signal.
[0072] Comparative Example 2: Au@Ti-MOF material with unmodified gold nanoparticle surface
[0073] This comparative example aims to verify the effect of surface modification on the growth of MOF shell. The preparation method is as follows:
[0074] First, a gold nanoparticle solution was prepared according to the method of Example 2. Subsequently, the surface modification step was skipped and the gold nanoparticles were directly dispersed in 125 parts by weight of DMF. Then, 12 parts by weight of tetraisopropyl titanate and 9 parts by weight of terephthalic acid were added to the dispersion, and the preparation was completed according to the subsequent steps of Example 2.
[0075] Compared with Example 2, the surface of the gold nanoparticles in this comparative example was not modified with 3-mercaptopropionic acid. The results showed that the MOF shell grew unevenly and some of the gold nanoparticle surfaces were not completely coated. The specific surface area of the material was reduced to 900 m 2 / g, pore volume is 0.7cm 3 In the cycle stability test, the performance of the material decreased by 30% after 10 cycles, while that of Example 2 only decreased by 5%. This shows that surface modification is crucial to the formation of a stable core-shell structure.
[0076] Comparative Example 3: Au@Ti-MOF material with too short MOF reaction time
[0077] This comparative example is intended to verify the effect of MOF growth time on material properties. The preparation method is basically the same as Example 3, but the reaction time in step (3) is shortened from 48 hours to 6 hours.
[0078] The results showed that the MOF shell thickness was only 50nm and the specific surface area was reduced to 1000m 2 / g, pore volume is 0.8cm 3 / g. In the gas sensing test, the detection limit for CO2 is 20ppm, while Example 3 can reach 5ppm. This shows that sufficient MOF growth time is crucial for forming a complete porous structure and improving sensing performance.
[0079] Comparative Example 4: Au@Zr-MOF materials using other metal sources
[0080] This comparative example is intended to verify the uniqueness of the titanium source. The preparation method is the same as that of Example 4, but tetraisopropyl titanate is replaced by an equimolar amount of zirconium chloride.
[0081] The MOF shell thickness of the obtained material is 100nm and the specific surface area is 1000m 2 / g, pore volume is 0.75cm 3 In the light responsiveness test, the configuration change of the material under ultraviolet light irradiation is only 60% of that in Example 4. This proves the advantage of titanium-based MOF in light responsiveness, thus supporting the rationality of the selection of titanium source in the present invention.
[0082] Comparative Example 5: Au@Ti-MOF material with too low amount of organic ligand
[0083] This comparative example is intended to verify the effect of the amount of organic ligand on the material structure. The preparation method is basically the same as Example 1, but the amount of terephthalic acid in step (3) is reduced from 3 parts by weight to 0.5 parts by weight.
[0084] The results showed that the MOF structure was incomplete and the shell thickness was uneven, with an average thickness of only 20nm. The specific surface area of the material dropped to 500m 2 / g, pore volume is 0.3cm 3 / g. In the selectivity test, the material's ability to distinguish molecules with similar structures decreased significantly, indicating that sufficient organic ligand dosage is crucial for forming a regular MOF structure and improving molecular recognition ability.
[0085] Comparative Example 6: Au@Ti-MOF material with insufficient activation treatment
[0086] This comparative example is intended to verify the effect of activation treatment on material properties. The preparation method is basically the same as Example 4, but the final activation treatment step is omitted.
[0087] The specific surface area of the obtained material is 900m 2 / g, pore volume is 0.6cm 3 / g, which is significantly lower than that of Example 4. In the dynamic response test, the response time of the material is 90 seconds, while that of Example 4 is only 30 seconds. This fully demonstrates the important role of activation treatment in removing residual solvents, increasing porosity and improving sensing performance.
[0088] Through the above six comparative examples, we systematically verified the influence of key factors such as the presence of gold core, surface modification, MOF growth time, metal source selection, organic ligand dosage, and activation treatment on the performance of adaptive Au@Ti bifunctional core-shell MOF sensing materials. The results show that there is a significant synergistic effect between the various technical features of the present invention.
[0089] In order to comprehensively evaluate the performance and superiority of the adaptive Au@Ti dual-functional core-shell MOF sensing material of the present invention, we designed a series of test experiments.
[0090] 1. Structural Characterization
[0091] First, we performed detailed structural characterization of all samples, including transmission electron microscopy (TEM) observation, X-ray diffraction (XRD) analysis, and nitrogen adsorption-desorption tests.
[0092] Experimental methods:
[0093] (a) TEM observation: A JEOL JEM-2100F field emission transmission electron microscope was used with an accelerating voltage of 200 kV. The sample was dispersed in ethanol by ultrasound and then dropped onto a carbon-supported copper grid.
[0094] (b) XRD analysis: using a Bruker D8 Advance diffractometer with a CuKα radiation source, a scanning range of 2θ=5-50°, a step length of 0.02°, and 1 s per step.
[0095] (c) Nitrogen adsorption-desorption test: Micromeritics ASAP 2020 equipment was used, the test temperature was 77 K, and the sample pretreatment condition was vacuum degassing at 150 °C for 12 h.
[0096] Result analysis:
[0097] TEM observation results show that the samples of Examples 1-4 all present obvious core-shell structures, with the gold core presenting a dark color and surrounded by a lighter MOF shell layer. In Comparative Example 1, only MOF particles were observed due to the lack of gold core. The integrity and uniformity of the core-shell structures of Comparative Examples 2-6 are not as good as those of the Examples.
[0098] XRD analysis results confirmed the presence of MOF structure in all samples, and characteristic diffraction peaks of gold were also observed in Examples 1 to 4 and Comparative Examples 2 to 6. The intensity and sharpness of the MOF diffraction peaks in the examples were better than those in the comparative examples, indicating that they had higher crystallinity.
[0099] The results of nitrogen adsorption and desorption tests are shown in Table 1:
[0100] Table 1. Specific surface area and pore structure parameters of the samples
[0101]
[0102] The results show that the specific surface area and pore volume of the embodiments are generally higher than those of the comparative examples, which is due to the synergistic effect of the optimized synthesis process and the core-shell structure.
[0103] 2. Optical property test
[0104] To verify the plasmon resonance effect of the gold core and the photoresponsiveness of the MOF shell, we conducted UV-Vis absorption spectroscopy tests and photoinduced configuration change experiments.
[0105] Experimental methods:
[0106] (a) UV-Vis absorption spectra: Shimadzu UV-2600 spectrophotometer was used with a scanning range of 300-800 nm and a step length of 1 nm. The samples were dispersed in ethanol for testing.
[0107] (b) Photoinduced configuration change: The sample was dispersed in ethanol and irradiated with a 365 nm UV lamp. The UV-Vis spectrum was measured every 5 minutes for 30 minutes.
[0108] Result analysis:
[0109] UV-Vis spectra show that Examples 1-4 all have obvious plasma resonance absorption peaks at 520-550nm, while this peak is not observed in Comparative Example 1 due to the lack of gold cores. The absorption peak intensity and position of Comparative Examples 2-6 are not as ideal as those of the Examples.
[0110] Under ultraviolet light irradiation, the absorption intensity in the range of 400-450nm of Examples 1-4 gradually increased over time, indicating that the MOF structure underwent a reversible configuration change. Among them, Example 3 showed the most significant change, with the absorption intensity increasing by 40% after 30 minutes. In contrast, the changes in the comparative examples were generally smaller, with Comparative Example 4 only increasing by 24%.
[0111] These results confirm the excellent optical properties of the material of the present invention, and the synergistic effect of the gold core and the MOF shell makes the material have significant photoresponsiveness.
[0112] 3. Sensing performance test
[0113] We selected three typical analytes (heavy metal ions Pb 2+ , glucose and CO2 gases) to evaluate the potential of the material in different application fields.
[0114] Experimental methods:
[0115] (a) Pb 2+ Detection: Prepare Pb with a concentration of 0-100ppb 2+ Solution: 5 mg of sample was dispersed in 10 mL of solution, stirred at room temperature for 30 minutes, and the fluorescence spectrum of the solution was measured (excitation wavelength 365 nm).
[0116] (b) Glucose detection: Glucose solution with a concentration of 0-10 mM was prepared, 5 mg of the sample was dispersed in 10 mL of the solution, incubated at 37°C for 30 min, and the UV-Vis absorption spectrum of the solution was measured.
[0117] (c) CO2 detection: 10 mg of sample was pressed into a thin sheet, placed in a gas sensor, CO2 gas of different concentrations (0-1000 ppm) was introduced, and the resistance change was measured.
[0118] Result analysis:
[0119] Table 2. Sensing performance parameters of samples
[0120]
[0121] The sensing performance of the examples is generally better than that of the comparative examples. Among them, Example 3 performs best, which may be due to its largest specific surface area and pore volume, providing more active sites. It is worth noting that Examples 1-4 have a good performance on Pb 2+ The detection limits are all lower than 1ppb, meeting the requirements of drinking water standards and demonstrating extremely high sensitivity.
[0122] 4. Stability and repeatability test
[0123] To evaluate the practical application potential of the material, we conducted cyclic stability and chemical stability tests.
[0124] Experimental methods:
[0125] (a) Cyclic stability: Pb 2+ Taking the detection as an example, the same sample was repeatedly used for 10 detections and washed with EDTA solution after each detection.
[0126] (b) Chemical stability: The samples were immersed in buffer solutions of pH = 4 and pH = 10 for 7 days, respectively, to test the changes in material structure and performance.
[0127] Result analysis:
[0128] The cyclic stability test showed that after 10 cycles, the detection sensitivity of Examples 1-4 decreased by less than 10%. Among them, Example 3 performed best, with a decrease of only 5%. In contrast, the sensitivity of Comparative Example 2 decreased by 30% after 10 cycles, and the performance degradation of other comparative examples was generally greater than that of the Examples.
[0129] The results of the chemical stability test showed that Examples 1-4 maintained good structural integrity in both acidic and alkaline environments, and no significant changes were observed in the XRD patterns. Performance tests showed that after immersion under extreme pH conditions for 7 days, the detection sensitivity of the Examples decreased by no more than 15%. In contrast, Comparative Example 4 showed obvious structural collapse under alkaline conditions, and the detection sensitivity decreased by 40%.
[0130] These results demonstrate the excellent stability and reusability of the materials of the present invention, which is due to the strong interaction between the gold core and the MOF shell, as well as the optimized synthesis process.
[0131] In summary, through a series of systematic testing experiments, we have comprehensively evaluated the performance of the adaptive Au@Ti dual-functional core-shell MOF sensing material. The results show that the material of the present invention has excellent performance in structural characteristics, optical properties, sensing performance and stability, far exceeding the comparative samples. It is particularly worth mentioning that we have found the following unexpected technical effects:
[0132] 1. Ultra-high detection sensitivity: Example 3 for Pb 2+ The detection limit reached 0.2 ppb, which is much lower than that of similar materials reported previously. This may be due to the synergistic enhancement effect of the plasmon resonance effect of the gold core and the molecular recognition ability of the MOF shell.
[0133] 2. Excellent photoresponsiveness: The embodiments show rapid and reversible configurational changes under UV light irradiation, which provides the possibility for the development of new light-controlled sensors.
[0134] 3. Multiple selectivity: The material of the present invention exhibits high sensitivity to heavy metal ions, biological molecules and gases at the same time. This multifunctionality is difficult to achieve with other single-component materials.
[0135] 4. Excellent stability: The material remains highly stable under extreme pH conditions, which greatly expands its potential application range.
[0136] These unexpected technical effects can be explained by the unique structure and synergy of the materials. The gold core not only provides a plasma enhancement effect, but also may regulate the electronic structure of MOF through electron transfer. The MOF shell provides efficient molecular recognition through controllable pore structure and surface chemistry. The interface effect between the two may generate new active sites, further improving the performance of the material.
[0137] In general, the adaptive Au@Ti bifunctional core-shell MOF sensing material of the present invention exhibits excellent comprehensive performance and has broad application prospects in the fields of environmental monitoring, biosensing and gas detection.
[0138] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an adaptive Au@Ti dual-functional core-shell MOF sensing material, characterized in that: The following steps are involved: (1) First, 1-5 parts by weight of chloroauric acid is dissolved in 100-500 parts by weight of deionized water, stirred at 80-90° C., and 2-10 parts by weight of an aqueous solution of trisodium citrate is quickly added, and reacted for 15-30 minutes to obtain a gold nanoparticle solution; (2) Next, slowly dropwise adding 0.5-3 parts by weight of 3-mercaptopropionic acid ethanol solution into the gold nanoparticle solution, stirring at room temperature for 4-6 hours, centrifugally separating, washing, and then dispersing in 50-200 parts by weight of N,N-dimethylformamide; (3) Then, 5-20 parts by weight of tetraisopropyl titanate and 3-15 parts by weight of terephthalic acid are added to the dispersion, and after ultrasonic dispersion, the dispersion is transferred to a high-pressure reactor and reacted at 120-180° C. for 12-48 hours; (4) Again, the reaction product is centrifuged, washed, vacuum dried at 60-80° C. for 12-24 hours, and ground and sieved; (5) Finally, the adaptive Au@Ti bifunctional core-shell MOF sensing material is obtained by activation treatment at 150-200°C and 0.1-1 kPa for 8-12 hours.
2. The preparation method according to claim 1, characterized in that: In the step (1), trisodium citrate is dissolved in 10-50 parts by weight of water.
3. The preparation method according to claim 1, characterized in that: In the step (2), 3-mercaptopropionic acid is dissolved in 5-30 parts by weight of ethanol.
4. The preparation method according to claim 1, characterized in that: In the step (2), the centrifugal separation is performed at 10,000 rpm for 10 minutes.
5. The preparation method according to claim 1, characterized in that: In the step (3), the ultrasonic treatment time is 15-30 minutes.
6. The preparation method according to claim 1, characterized in that: In the step (3), the centrifugal separation is performed at 8000 rpm for 15 minutes.
7. The preparation method according to claim 1, characterized in that: In the step (4), the product is dispersed in 100-300 parts by weight of ethanol and dried.
8. The preparation method according to claim 1, characterized in that: In the step (4), the product is ground and then passed through a 200-mesh sieve.
9. The adaptive Au@Ti dual-functional core-shell MOF sensing material prepared by the method according to any one of claims 1 to 8.
10. The adaptive Au@Ti dual-functional core-shell MOF sensing material according to claim 9, characterized in that: The gold core size of the material is 20-50nm, the MOF shell thickness is 50-200nm, and the specific surface area is 800-1500m 2 / g, pore volume is 0.5-1.2cm 3 / g, and the main pore size distribution is 1-3nm.
Citation Information
Patent Citations
Dumbbell-shaped gold nano bipyramid / titanium dioxide nano composite material and preparation method thereof
CN108704642A
Au-coated Ni-MOF composite material with core-shell structure as well as preparation method and application of Au-coated Ni-MOF composite material
CN117448882A
Preparation method of silicon dioxide with hierarchical pore structure
CN118529737A
GOLD LOADED TiO2 NANOTUBE-MULTIWALLED CARBON NANOTUBE COMPOSITES AS ACTIVE PHOTOCATALYSTS FOR CYCLOHEXANE OXIDATION
US20160214087A1
Metal-organic framework dispersion production method, metal-organic framework dispersion, and metal-organic framework composition including metal-organic framework dispersion
WO2024048308A1